2022
DOI: 10.1128/mbio.00615-22
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Associated Antigen 9 Promotes Influenza A Virus-Induced Cell Death via the c-Jun N-Terminal Kinase Signaling Pathway

Abstract: Upon influenza A virus (IAV) infection, DAI is activated, recruits downstream proteins to assemble a multiprotein platform (PANoptosome), and then triggers cell death. Until now, the protein composition and assembly mechanism of the PANoptosome during IAV infection had not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Del Sarto et al recently have identified an increase of phosphorylaton at Ser730 in JIP4 after Influenza A virus infection (80). Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway (81). Thus, there is a correlation between c-jun phosphorylation and SPAG9 (JIP4) phosphorylation after Influenza A virus infection.…”
Section: Discussionmentioning
confidence: 88%
“…Del Sarto et al recently have identified an increase of phosphorylaton at Ser730 in JIP4 after Influenza A virus infection (80). Similarly, other work has recently described that this phosphorylation promotes cell death via c-jun kinase signaling pathway (81). Thus, there is a correlation between c-jun phosphorylation and SPAG9 (JIP4) phosphorylation after Influenza A virus infection.…”
Section: Discussionmentioning
confidence: 88%